Implementing Website Simulation-Assisted Practicum on Students’ Psychomotoric Learning Outcomes - Sekar Ganda Ning Tyas Arum; Etika Dyah Puspitasari; Much Fuad Saifuddin (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
Practicum is an important learning activity to train students' psychomotor skills. Therefore, students' ability to understand the steps and methods of practice in the laboratory must be familiarized. The use of website-based practicum simulation is one of the learning media to prepare students before entering the real laboratory. The purpose of this study was to determine the effect of website simulation-assisted practicum on students' psychomotor learning outcomes in class XI food ingredient test practicum. The type of research used was quasi experiment with Posttest non-equivalent control groups design. The population used was 187 students and the sampling technique was purposive sampling. The sample used was 56 students, with XI MIPA 1 as the control and XI MIPA 2 as the experimental class. The data analysis technique used Independent t-test statistical analysis. The results showed that the implementation of web-based practicum simulation had a significant effect on all four psychomotor levels. The experimental class obtained higher results than the control class.